Very-high-power short-duration ablation for treatment of premature ventricular contractions – The FAST-AND-FURIOUS PVC study. (June 2022) - Heeger, Christian-Hendrik; Popescu, Sorin S.; Kirstein, Bettina; Hatahet, Sascha; Traub, Anna; Phan, Huong-Lan; Feher, Marcel; D́Ambrosio, Gabriele; Keelani, Ahmad; Schlüter, Michael; Vogler, Julia; Eitel, Charlotte; et al.
Abstract: Objectives: We sought to assess the efficacy, safety and short-term clinical outcome of very high-power short-duration (vHP-SD) radiofrequency (RF) catheter ablation for the treatment of idiopathic PVCs originating from the cardiac outflow tract (OT). Background: Power-controlled RF ablation is a widely used technique for the treatment of premature ventricular contractions (PVCs). A novel ablation catheter offers three microelectrodes and six thermocouples at its tip and provides temperature-controlled vHP-SD (90 Watts/4 s, ) with the opportunity to switch to moderate-power mode. Methods: In this pilot study, twenty-four consecutive, prospectively enrolled patients underwent PVC ablation utilizing the vHP-SD ablation (study group) and were compared with 24 consecutive patients previously treated with power-controlled ablation (control group). Each group included 12 patients with PVCs originating from the right ventricular OT (RVOT) and 12 patients with PVCs originating from the left ventricular OT (LVOT). The acute endpoint was PVC elimination and was achieved in all patients. Results: In 16/24 (67%) patients (study group) it was achieved by using vHP-SD only. The median RF delivery time was 52 (interquartile range [IQR] 16, 156) seconds (study group) and 350 (IQR 240, 442) seconds (control group, p < 0.0001). No difference was observed regarding procedure duration (p = 0.489) as well as 6-months follow-up (p = 0.712). One (4%, study group) and 2 (8%, control group) severe adverse events occured (p = 0.551). Conclusion: In this study, vHP-SD PVC ablation was similarly effective and safe as compared to conventional power-controlled ablation. The RF time was significantly shorter.